Beyond N and P: The impact of Ni on crude oil biodegradation. (December 2019) - Mejeha, Obioma K.; Head, Ian M.; Sherry, Angela; McCann, Clare M.; Leary, Peter; Jones, D. Martin; Gray, Neil D.
Abstract: N and P are the key limiting nutrients considered most important for the stimulation of crude oil degradation but other trace nutrients may also be important. Experimental soil microcosms were setup to investigate crude oil degradation in the context of Ni amendments. Amended Nickel as NiO, NiCl2, or, a porphyrin complex either inhibited, had no effect, or, enhanced aerobic hydrocarbon degradation in an oil-contaminated soil. Biodegradation was significantly (95% confidence) enhanced (70%) with low levels of Ni-Porph (12 mg/kg) relative to an oil-only control; whereas, NiO (200 and 350 mg/kg) significantly inhibited (36 and 87%) biodegradation consistent with oxide particle induced reactive oxygen stress. Microbial community compositions were also significantly affected by Ni. In 16S rRNA sequence libraries, the enriched hydrocarbon degrading genus, Rhodococcus, was partially replaced by a Nocardia sp. in the presence of low levels of NiO (12 and 50 mg/kg). In contrast, the highest relative and absolute Rhodococcus abundances were coincident with the maximal rates of oil degradation observed in the Ni-Porph-amended soils. Growth dependent constitutive requirements for Ni-dependent urease or perhaps Ni-dependent superoxide dismutase enzymes (found in Rhodococcus genomes) provided a mechanistic explanation for stimulation. These results suggest biostimulation technologies, in addition to N and P, should also consider trace nutrients such as Ni tacitly considered adequately supplied and available in a typical soil. Graphical abstract: Image 1 Highlights: Ni concentration and form added to soil dictated impacts on oil biodegradation. Biodegradation was enhanced with low concentrations of porphyrin-complexed Ni (12 mg/kg). At higher concentrations, Ni oxide but not porphyrin-complexed Ni was inhibitory. Highest Rhodococcus abundances were coincident with porphyrin-complexed Ni stimulation.